Karakteristik Pola Aliran Air-Udara, Campuran Air+Gliserin (G20)-Udara, dan Campuran Akuades+Butanol 4%-Udara Pada Pipa Horizontal Berukuran Mini - Jayadi, Farid; Sudarja, Sudarja; Komolosari, Eli (universitas teuku umar, 2022)
This study aims to obtain information about the flow characteristics of Water-Air Flow, Mixture of Glycerin+Water(G20)-Air, and Mixture of Aquadest+Butanol 4%-Air. The two-phase flow characteristics in mini-sized pipes have significant differences with the two-phase flow characteristics in conventional pipes, so it will affect fluid distribution processes involving two-phase flow such as heat transfer processes. Therefore, it is necessary to conduct further studies on the two-phase flow pattern in mini-sized pipes. This research was conducted in a test section in the form of a glass pipe with a diameter of 1.6 mm in a horizontal position. The liquid fluid used is water which has a surface tension (σ) of 71 mN/m, a mixture of glycerin+water (G20) has a surface tension (σ) of 62.5 mN/m, and a mixture of distilled water+butanol 4% has a surface tension (σ) of 36.50 mN/m. Superficial velocity of gas (JG)=0.033–4.935 m/s, and superficial velocity of liquid (JL)=0.025–66.3 m/s. The results showed that stratified flow was not observed in the mini channel as can be found in conventional pipes. The detected flow patterns are: bubbly, slug, slug-annular, churn, and annular. The results of flow pattern maps compared with flow pattern maps from Triplett et al (1999a), Chung and Kawaji (2004) and Sudarja et al (2014), and Aqli et al (2015) show that the higher the viscosity, the higher the annular churn-slug flow transition line will be. decreases while the annular – slug annular transition line tends to be more sloping.